Battery ultra-fast charging protocol (UFC) of lithium-ion batteries (LIB) - Salman Taha Aljunied (Nanyang Technological University, 2022)
An adaptive fast-charging protocol for lithium-ion batteries named NLV (Non-Linear Voltammetry) have been proven to not only be able to fast charge a battery in a targeted time but has also been shown that it does not degrade the performance of the battery as much as other fast charging protocol does. While experiments on single cells have been undertaken, it is critical to determine if NLV applies to multicell battery systems. The performance of a single cell system was compared to that of a multicell system. To explore the variations of current, voltage, temperature, and capacity, the setup monitored and recorded them in real time. The investigation revealed that NLV done in parallel and series exhibited characteristics identical to those of a single cell system, validating the NLV procedure on a multicell layout. Additionally, temperatures observed in most tests demonstrate a gradual increase with all temperatures remaining below 50 degrees at the conclusion of the cycle, which is critical for a battery's performance and safety. However, it was observed that some of the tests conducted were not able to meet the charging time requirement. This can be due to several factors such as NLV optimisation, battery internal properties or power supply which needs to be investigated. Further analysis on aging and multiple cycle tests is also required for long term usage.